IDE FEMINISME DALAM NOVEL THE MOTHER KARYA PEARL S. BUCK - PONTO, RINA APRILIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œIdeas of Feminism Revealed in The Novel The Mother by Pearl S. Buckâ€ is written to find out the ideas of feminism. Feminism has an important role in society and culture. The problem to be researched is how the ideas of feminism revealed in the novel The Mother. The objective of this research is to identify, analyze and give explanation about the ideas of feminism revealed through the main female character, the mother, in the novel The Mother. The method of this research is descriptive. Intrinsic approach is applied in analyzing character the mother by using Robertâ€™s theory, setting and plot. To analyze the ideas, the writer uses extrinsic approach, the theory of relation between literature and idea from Wellek and Warren. Â  The result of this research reveals that most of the actions done by the character of the mother show her as a strong female figure where she was able enter the whole aspects of her life, she became a mother and being a father and even she herself became the backbone of the family. The mother is able to defend her rights as a woman even though she often get mistreatment of those around her and even her own family. Ideas of feminism revealed through the character, plot and setting. Also, the relation between tradition of Chinese and the background of Chinese live in 1930â€™s are identified to found out the ideas of feminism. Â  Â  Key Words: Feminism, Novel and Character.